ANALISIS PROSES PEMBELAJARAN POKOK BAHASAN ELEKTROKIMIA DI KELAS XII SMAN 1 PANTI - Indang Dewata (Ta'dib, 2011)
The purpose of this research was to analyze the learning process of electrolysis cell matter which covered the planning, implementation, and evaluation; and analysis of theunderstanding of students’ concept (conception)  as well as the finding of the cause of the misconceptions and not understanding in matter of electrolysis cell. The study used was descriptive analysis. It was used to answer the problem’s formulation in this study. The object of this research were the process of learning and students’ conceptions. The subjects of this study were students in grade XII IA I and IA II and chemistry teacher in grade XII IA at SMAN 1  Panti. Instruments in this study were the observation guide, a recorder (Handycam) and two tier diagnostic test.Based on the data analysis, it is found that (1) learning process in the electrolysis cell matter in SMAN 1 Panti was not in accordance with the standards of process (2) Students IA I and IA II had misconceptions and did not understand the whole concept in electrolysis cell matter. (3) The cause of misconceptions and not understanding of students were mainly the teachers and students. The learning process should be conducted in accordance with the standards of process that has been established by government in order to ensure learning carried out effectively, so the quality of learning can be improved.Kata kunci: analisis, proses pembelajaran, elektrokimia